Melansporellaceae: a novel family of Diaporthales (Ascomycota) - Du, Zhuo; Hyde, Kevin D.; Yang, Qin; Liang, Ying-Mei; Tian, Cheng-Ming (Phytotaxa, 2017)
Melansporellaceae fam. nov. is introduced to accommodate a genus of diaporthalean fungi that is a phytopathogen causing walnut canker disease in China. The family is typified by Melansporella gen. nov. It can be distinguished from other diaporthalean families based on its irregularly uniseriate ascospores, and ovoid, brown conidia with a hyaline sheath and surface structures. Phylogenetic analysis shows that Melansporella juglandium sp. nov. forms a monophyletic group within Diaporthales (MP/ML/BI=100/96/1) and is a new diaporthalean clade, based on molecular data of ITS and LSU gene regions. Thus, a new family is proposed to accommodate this taxon.